The Integration of Charismata and Stewardship as the Foundation of Transformative Christian Leadership in the Contemporary Church - Paul Stefan Maabuat (International Forum of Researchers and Lecturers, 2025)
The integration of charismata and stewardship serves as a foundational framework for transformative leadership that is relevant to the contemporary church. This study examines how the synergy between charismatic expression and stewardship practices can strengthen church leadership that is transformative, inclusive, and adaptive to the challenges of the present age. The research employs a literature review and case study approach, accompanied by thematic analysis of interview data and relevant documents. The findings indicate that the integration of charismata and stewardship fosters positive change within the life of the church and the wider community, while also supporting spiritual growth and active congregational engagement in ministry. The theological and practical implications of this integration are far-reaching, contributing both to the reinforcement of Christian leadership identity and to encouraging churches to develop leadership models that are transformative, innovative, and creative.